Risk factors for loss to follow-up in HIV care: A retrospective cohort study in Dili, Timor-Leste - Amaral, Benigna Veneranda da Costa Amaral; Yeom, Joon Sup; Machado, Filipe de Neri; Marques, Mariano da Silva; Soares, Noel Gama (Svāsthya: Trends in General Medicine and Public Health, 2025)
Loss to follow-up (LTFU) among people living with HIV/AIDS (PLWHA) is a public health challenge that reduces the effectiveness of antiretroviral therapy (ART), increases the risk of transmission, and contributes to increased mortality. This study aimed to identify the risk factors for LTFU among patients with HIV in Dili, Timor-Leste. This retrospective cohort study used secondary data from 150 HIV-positive patients at the Community Progress Association (AK-P) in Dili from 2014 to 2022. The inclusion criterion was adult patients aged ≥ 15 years who started ART with a minimum follow-up of 183 days. Descriptive statistics, chi-square tests, logistic regression, and Kaplan‒Meier analysis were used to identify the factors affecting LTFU. Of the 150 patients, 72% remained under care, 20.6% experienced LTFU, and 7.3% died. The majority were male (90%), with men who had sex with men (MSM) having a 40% lower risk of LTFU than female sex workers (FSW). Patients aged ≥54 years had a 21% lower risk, and married individuals had a 26% lower risk than single individuals did. High income and ART initiation were protective factors, while a CD4 count <200 cells/mm³ increased the risk of LTFU by 4.2 times, and a viral load >1000 copies/mL increased the risk by 2.79 times. Level 1 ART was associated with 97% survival at 1, 3, and 5 years, whereas level 2 ART was associated with only 3.6% survival in the first year. Sociodemographic and clinical variables influenced LTFU in HIV care in Timor-Leste.